Cardio-vocal Syndrome as a Complication Patient with Severe Mitral Regurgitation and Moderate Aortic Regurgitation with Pulmonary Hypertension - Adityo Basworo; Agus Subagjo (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACT Hoarseness due to paralysis of vocal cord, as in Cardio-vocal syndrome, is caused by mechanical affection of left recurrent laryngeal nerve from enlarged cardiovascular structures. Mitral valve prolapse is rarely found to cause this syndrome. Case report presenting a 47 years old male visited the outpatient department with a clinical history of dyspnea and hoarseness since a year ago. Physical examination revealed late systolic murmur in apex and low-grade diastolic murmur in right second intercostal space. Echocardiography confirmed severe mitral regurgitation due to flail anterior mitral valve leaflet with severe left atrium dilatation (9.0 cm) and moderate aortic regurgitation due to mal-coaptation of aortic valves. Laryngoscopy revealed an immobile left vocal cord. He underwent successful double valve replacement after three months follow up the patient showed improvement of hoarseness. The incidence of Cardio-vocal syndrome in mitral valve disease varies from 0.6% to 5%. In cases diagnosed with thoracic disease, paralysis of the left vocal cord was reported 1.75 times more frequent than the right side. The aim of this case report is we have to aware that Cardio-vocal syndrome is a rare cause of vocal cord paralysis and should be considered as a differential diagnosis of hoarseness, particularly if the patient has a cardiac history. Comprehensive evaluation and prompt treatment may allow reversal of the damage to left recurrent laryngeal nerve. Permanent nerve damage can occur due to late diagnosis. Keywords : Cardio-vocal syndrome, Mitral regurgitation, Aortic RegurgitationCorrespondence : adityobasworo@gmail.com